Intraoperative handheld optical coherence tomography forward-viewing probe: physical performance and preliminary animal imaging - Sun, Cuiru (Optical Society of America, 2012)
A prototype intraoperative hand-held optical coherence tomography (OCT) imaging probe was developed to provide micron resolution cross-sectional images of subsurface tissue during open surgery. This new ergonomic probe was designed based on electrostatically driven optical fibers, and packaged into a catheter probe in the form factor of clinically accepted Bayonet shaped neurosurgical probes. Optical properties of the probe were measured to have a ~20 μm spot size, 5 mm working distance and 4 mm field of view. Feasibility of this probe for structural and Doppler shift imaging was tested on porcine femoral blood vessel imaging.